2018
DOI: 10.1200/jgo.2016.009027
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Cancer in Northern Tanzania: Evaluation of Diagnosis, Treatment, and Outcomes

Abstract: PurposeThe majority of new diagnoses of pediatric cancer are made in resource-poor countries, where survival rates range from 5% to 25% compared with 80% in high-resource countries. Multiple factors, including diagnostic and treatment capacities and complex socioeconomic factors, contribute to this variation. This study evaluated the available resources and outcomes for pediatric patients with cancer at the first oncology treatment center in northern Tanzania.MethodsQualitative interviews were completed from J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 22 publications
4
39
0
Order By: Relevance
“…24,28,36 This is in contrast to previous studies from other African countries that reported lymphomas as the most common tumours affecting the paediatric population. 11,22,34 We found that the majority of children with lymphomas were older than 5 years, which is similar to the findings of a recent report from Yemen. 29 In HICs, CNS tumours are the second most diagnosed cancers and represent 20% to 27% of all paediatric cancers.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…24,28,36 This is in contrast to previous studies from other African countries that reported lymphomas as the most common tumours affecting the paediatric population. 11,22,34 We found that the majority of children with lymphomas were older than 5 years, which is similar to the findings of a recent report from Yemen. 29 In HICs, CNS tumours are the second most diagnosed cancers and represent 20% to 27% of all paediatric cancers.…”
Section: Discussionsupporting
confidence: 81%
“…10,28,32,33 This is in contrast to many LMICs, where leukaemias are much less frequent than lymphomas. 8,21,22,34 We found that most children with leukaemias were boys, which is also similar to that reported in other studies. 23,35 Most of the children in our analysis resided in rural regions of Sudan, where tertiary medical care is lacking.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In Mwanza, Tanzania, Bugando Medical Centre (BMC) serves as the area's Zonal consultant hospital, with a catchment area of the entire lake region [3] serving over 15 million people [4]. In the past ten years, BMC has worked to create, staff and train advanced oncology, surgery, and pathology departments to provide cancer diagnostic, treatment, and radiation services [2].…”
Section: Introductionmentioning
confidence: 99%
“…Historically, 2-year survival rates at BMC were 20%, with 52% of cancer diagnoses considered palliative at presentation, because of late presentation and limited diagnostic and therapeutic resources (K. Schroeder, personal communication, June 15, 2016). 13 No national health insurance plan exists in Tanzania, and 67.9% of the population lives below the poverty line. 14 , 15 With the average cost of a cancer diagnosis and treatment at $560 per patient, 16 most caregivers cannot afford life-saving interventions for patients, resulting in a large number of terminally ill children in Tanzania.…”
Section: Introductionmentioning
confidence: 99%